2010
DOI: 10.1007/s12350-010-9291-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative analysis and interpretation of CT perfusion imaging

Abstract: Coronary artery disease (CAD) remains the leading cause of death in the United States. Rest and stress myocardial perfusion imaging has an important role in the non-invasive risk stratification of patients with CAD. However, diagnostic accuracies have been limited, which has led to the development of several myocardial perfusion imaging techniques. Among them, myocardial computed tomography perfusion imaging (CTP) is especially interesting as it has the unique capability of providing anatomic- as well as coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In addition, newer scanning techniques have allowed assessment of perfusion and FFR by CCTA alone, in addition to coronary anatomy. [195][196][197][198][199][200][201] Notably, these combined assessments allow for a fused image in which the physiological assessment of flow is coupled with the anatomic extent and severity of CAD and also provides information on plaque composition and arterial remodeling. Limited evidence is available on hybrid imaging, although several reports have reported prognostic accuracy for cardiac events with both ischemic and anatomic markers.…”
Section: Hybrid Imagingmentioning
confidence: 99%
“…In addition, newer scanning techniques have allowed assessment of perfusion and FFR by CCTA alone, in addition to coronary anatomy. [195][196][197][198][199][200][201] Notably, these combined assessments allow for a fused image in which the physiological assessment of flow is coupled with the anatomic extent and severity of CAD and also provides information on plaque composition and arterial remodeling. Limited evidence is available on hybrid imaging, although several reports have reported prognostic accuracy for cardiac events with both ischemic and anatomic markers.…”
Section: Hybrid Imagingmentioning
confidence: 99%
“…Investigators demonstrated a strong correlation of EBCT-derived myocardial perfusion metrics with microsphere-derived MBF [57-59]. Dynamic EBCT was further validated in an animal study and in healthy volunteers with maximal vasodilatation and at rest [60].…”
Section: Ct Quantitative Perfusion Imagingmentioning
confidence: 99%
“…The window and level are initially set to 300 and 150, respectively, based on experience and on typical values described in the literature (e.g., Valdiviezo et al [8] and Cury et al [13]) and considering that common starting values should be used for all exams contributing to similar analysis conditions and criteria. If desired, window and level can be adjusted at any time.…”
Section: Single Cardiac Phase Perfusion Assessmentmentioning
confidence: 99%
“…While some efforts are being directed to the development of such methods [6,7] for quantitative myocardial perfusion assessment, to the best of our knowledge, none of those works considered providing enhanced tools to support the clinician during visual assessment. Visual interpretation of CTP images is still of paramount importance [8], given the common presence of image artefacts [5,9] which hinder a good performance of automatic methods (among other factors). Introducing interactive tools to support visual perfusion assessment might, for example, reduce the required clinician effort to correctly assign perfusion deficit to a specific myocardial segment, shortening analysis time and improving confidence levels.…”
Section: Introductionmentioning
confidence: 99%